English for teens: o redesign dos recursos semióticos na adaptação de um curso de inglês on-line para adolescentes - Robaina, Natália Lopes (2023)
The coronavirus pandemic has forced several educational institutions to adopt the emergency remote teaching regime, making it necessary to develop didactic materials for this new reality. The current ongoing master's research aims to adapt one of Labeon's English courses, originally offered in a hybrid approach, for its delivery in distance education, mainly by implementing a combination of different multimodal resources to create engaging spaces that promote student autonomy and interaction in the course. Thus, this research constitutes a qualitative-quantitative investigation of an exploratory and descriptive nature. Regarding the technical procedures, a participatory action research approach was adopted, using a mixed-method approach, where adolescent students between the ages of 14 and 17, from public schools in the Santa Maria region, participated in the course for testing. Data were collected and analyzed through observation and the administration of questionnaires, addressing issues related to the course and the digitally developed and adapted teaching materials, involving the assessment of users regarding the proposed material redesign based on Keller's ARCS model (2006). Based on the information obtained from this evaluation and analysis, the course underwent further adjustments as necessary. The results demonstrated the potentialities and challenges of implementing online language courses, especially with the teenage audience. The changes facilitated a stronger connection between the students and the content, encouraging greater involvement and engagement. The use of semiotic resources, such as videos, gifs, and images, played a crucial role in making the learning experience more dynamic and attractive. Video lessons stood out as a valuable resource, providing better comprehension of the topics covered. Although overall evaluations were positive, the research also highlighted significant challenges in implementing online courses with teenagers, emphasizing the need to address them to further enhance the educational experience. Thus, it is concluded that the presence of multimodality in redesigning courses for online learning presents significant potential to overcome limitations and promote an interactive and engaging learning experience. Research investigating the impact of emerging technologies on the learning experience is essential to drive distance education forward, making it increasingly effective and adaptable to contemporary challenges and demands.